Sphagnum Inspired g‐C3N4 Nano/Microspheres with Smaller Bandgap in Heterojunction Membranes for Sunlight‐Driven Water Purification. Issue 12 (15th February 2021) - Ji, Lingtong; Yan, Luke; Chao, Min; Li, Mengru; Gu, Jincui; Lei, Miao; Zhang, Yanmei; Wang, Xun; Xia, Junyuan; Chen, Tianyu; Nie, Yujing; Chen, Tao
Abstract: Membrane separation is recognized as one of the most effective strategies to treat the complicated wastewater system for economic development. However, serious membrane fouling has restricted its further application. Inspired by sphagnum, a 0D/2D heterojunction composite membrane is engineered by depositing graphitic carbon nitride nano/microspheres (CNMS) with plentiful wrinkles onto the polyacrylic acid functionalized carbon nanotubes (CNTs‐PAA) membrane through hydrogen bond force. Through coupling unique structure and chemistry properties, the CNTs‐PAA/CNMS heterojunction membrane presents superhydrophilicity and underwater superoleophobicity. Furthermore, thanks to the J‐type aggregates during the solvothermal process, it is provided with a smaller bandgap (1.77 eV) than the traditional graphitic carbon nitride (g‐C3 N4 ) sheets‐based membranes (2.4–2.8 eV). This feature endows the CNTs‐PAA/CNMS membrane with superior visible‐light‐driven self‐cleaning ability, which can maintain its excellent emulsion separation (with a maximum flux of 5557 ± 331 L m −2 h −1 bar −1 and an efficiency of 98.5 ± 0.6%), photocatalytic degradation (with an efficiency of 99.7 ± 0.2%), and antibacterial (with an efficiency of ≈100%) ability even after cyclic experimental processes. The excellent self‐cleaning performance of this all‐in‐one membrane represents its potential value for water purification. Abstract : An advanced all‐in‐one separation membrane is presented. It endows with excellent self‐cleaning ability due to its smaller bandgap. Hence, the designed heterojunction membrane can realize continuous water purification with stable separation performance, catalytic degradation ability, and antibacterial capacity, suggesting its potential value for optimizing water environment.